1993
DOI: 10.1111/j.1442-9993.1993.tb00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between types of prey captured and growth form in Drosera in southwestern Australia

Abstract: Sympatrically growing species of Drosera were examined, including rosette forms, climbers and upright, self-supporting species, in southwestern Australia, to see whether the height above ground of the capturing leaves influenced the kinds of prey caught. The leaves examined for invertebrate prey remains were all collected at the same time and the results thus represent a snapshot of the prey situation. Although the number of fully opened, active leaves and leaf size among species varied 40-fold and 22-fold, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 3 publications
3
24
0
Order By: Relevance
“…Gluing seems to be the best way to capture prey with such escape capabilities, as it has been evolved in parallel in different springtail predators. For example, some carnivorous plants of the genus Drosera capture springtails with gluey mucilage, secreted by hair-like structures (Verbeek and Boasson, 1993). This glue exhibits rheological behaviour quite similar to that of the harvestman pedipalpal setae studied by us (Erni et al, 2011).…”
Section: Research Articlementioning
confidence: 89%
“…Gluing seems to be the best way to capture prey with such escape capabilities, as it has been evolved in parallel in different springtail predators. For example, some carnivorous plants of the genus Drosera capture springtails with gluey mucilage, secreted by hair-like structures (Verbeek and Boasson, 1993). This glue exhibits rheological behaviour quite similar to that of the harvestman pedipalpal setae studied by us (Erni et al, 2011).…”
Section: Research Articlementioning
confidence: 89%
“…To inform prey size classes for the autotomy experiment, preliminary field observations of in situ prey capture were undertaken for 58 D. collina individuals at a location in the Jarrah Forest east of Perth, Western Australia (GPS), in July 2017. Observations indicated that this species captured a similar spectrum of prey to that recorded previously for the closely related D. erythrorhiza (Dixon, Pate & Bailey, ; Verbeek & Boasson, ), predominantly small arthropods ranging from 1 mm to 1 cm in length (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Verbeek & Boasson (1993) found that the height above ground and the growth form of the capturing leaves influenced the types of prey caught in sympatrically growing Drosera species with different arrangement of adhesive traps, including rosette forms, climbers and upright, self‐supporting species. Prostrate species caught mainly walking, non‐aerial prey while self‐supporting and climbing species caught predominantly aerial prey (Verbeek & Boasson, 1993). Similarly, a trend towards specialization in prey composition in the genus Sarracenia , the North American pitcher plant, has been noted by several authors (Juniper et al , 1989 and references therein).…”
Section: Mechanisms To Reduce Pollinator‐prey Overlapmentioning
confidence: 99%